Optimizing Students' Conceptual Understanding on Electricity and Magnetism through Cognitive Conflict-Based Multimode Teaching (CC-BMT) - Samsudin, A.; Suhandi, A.; Rusdiana, D.; Kaniawati, I.; Fratiwi, N. J.; Zulfikar, A.; Muhaemin, M. H.; Hermita, N.; Mansur; Wibowo, F. C.; Supriyatman; Malik, A.; et al. (IOP PUBLISHING LTD, 2019)
Conceptual change is one of the international issues that had been studied by many researchers since three decades ago. Students' conceptual understanding could be optimized through the learning process in classroom. Nevertheless, students still have misconceptions that noticed the students conceptual change is still not successfully yet. In order to solve the problem, this study was conducted through four D research method (Define, Design, Develop and Disseminate) for 60 educational-university students that aimed to optimize students conceptual understanding using cognitive conflict-based multimode teaching (CC-BMT) in the learning process oriented conceptual change that concluded with: PDEODE*E worksheet design, simulation and natural phenomenon-based multimedia and Conceptual Change Text (CCT). The Electricity and Magnetism Conceptual Change Inventory (EMCCI) and CC-BMT have already been developed through the initial steps (define, design and develop) of four D model to produce the learning model that is able to optimize the students' conceptual understanding. Finally, in the disseminate phase, the quantitative data which is analyzed by using conceptual change process based on the score as the the percentage result of EMCCI four tier diagnostic test. The analyzing data which is utilized a sequential codding analysis reports for electricity and magnetism that the students misconceptions (M) -18.33% and -15%; sound understanding (SU) 25% and 11.67%; partial understanding (PU) 16.67% and 20%; no understanding (NU) 23.33% and 16.67%; uncodeable (UC) is all 0% after implementing the CC-BMT learning strategy. It can be concluded that the implementing of CC-BMT is able to optimize students' understanding on electricity and magnetism.
Keywords: FIELD; Physics